2009
DOI: 10.1063/1.3126485
|View full text |Cite
|
Sign up to set email alerts
|

Electron dynamics in films made of transition metal nanograins embedded in SiO2: Infrared reflectivity and nanoplasma infrared resonance

Abstract: We report on near normal infrared reflectivity spectra of ~550 nm thick films made of cosputtered transition metal nanograins and SiO 2 in a wide range of metal fractions. Co 0.85 (SiO 2 ) 0.15 ,with conductivity well above the percolation threshold has a frequency and temperature behavior according to what it is find in conducting metal oxides. The electron scattering rate displays an unique relaxation time characteristic of single type of carriers experiencing strong electron-phonon interactions. Using small… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…(pseudocubic Pmcm Z=1) [12] Overall, we find that our 1-emissivity spectra show remarkable similarities with the known behavior bulk disordered conducting oxides undergoing a metal to insulating phase transition (Fig. 7 in [21]). It suggests that a quantitative analysis of the high temperature mid-infrared real part of the optical conductivity, eq.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…(pseudocubic Pmcm Z=1) [12] Overall, we find that our 1-emissivity spectra show remarkable similarities with the known behavior bulk disordered conducting oxides undergoing a metal to insulating phase transition (Fig. 7 in [21]). It suggests that a quantitative analysis of the high temperature mid-infrared real part of the optical conductivity, eq.…”
Section: Resultssupporting
confidence: 73%
“…Overall, we find that our 1-emissivity spectra show remarkable similarities with the known behavior of bulk disordered conducting oxides undergoing a metal to insulating phase transition (figure 7 in [21]). This suggests that a quantitative analysis of the high temperature mid-infrared real part of the optical conductivity, equation (7), within a small polaron context, may help to identify phonon groups involved in main carrier-phonon interactions.…”
Section: Resultssupporting
confidence: 71%
“…81 To reproduce the full mid-infrared spectral region, we then allowed the possibility of more than one vibrational contribution using an empirical approach shown successful when applied to other distorted perovskites and glassy systems. 82,83,84 This results in the convoluted addition of bell shaped uncorrelated individual contributions in the region from 1000 cm -1 to 9000 cm -1 , each calculated at a phonon frequency j associated to the strength j at a temperature T.…”
Section: E Small Polaron and Higher Temperature Bipolaronsmentioning
confidence: 99%
“…26 A bipolaron is made of two small polarons in association as two carrier self-trapped localized bound pair, in which the common potential exceeds their Coulomb repulsion. 84 In this regime the confinement energy of small bipolarons is double relative to that in small polarons because the presence of the second electron, i.e., the depth of the well that self-traps both carriers is twice as deep. Their effective mass is expected to be also much larger than the hundred-fold increments of the electron mass expected for small polarons.…”
Section: E Small Polaron and Higher Temperature Bipolaronsmentioning
confidence: 99%
“…The influence of tunnelling charge transfer phenomena on infrared and/or optical absorption has to our knowledge, not been studied. Recently it has been suggested that the infrared properties of nanocomposites should be described using concepts used for transition metal oxides 43 , implying that a purely electrostatic theory may be insufficient. It is conceivable that such processes could "steal" resonance strength from the SDF, thus leading to a lower computed than experimental volume fraction of a nanocomposite.…”
Section: Spectral Density Functionsmentioning
confidence: 99%